The senescence-associated secretory phenotype mediates oncogene-induced senescence in pediatric pilocytic astrocytoma - Buhl, Juliane; Selt, Florian; Hielscher, Thomas; Ecker, Jonas; Sahm, Felix; Ridinger, Johannes; Usta, Diren; Wefers, Annika K.; Remke, Marc; Pusch, Stefan; Oehme, Ina; Tilburg, Cornelis M. van; et al. (Clinical cancer research, 2019)
Pilocytic astrocytoma (PA) is the most common childhood brain tumor, characterized by constitutive MAPK activation. MAPK signaling induces oncogene-induced senescence (OIS), which may cause unpredictable growth behavior of PAs. The senescence-associated secretory phenotype (SASP) has been shown to regulate OIS, but its role in PA remains unknown.